RETRACTED: Work on a literary text is one of the effective methods of independent work when teaching the Russian language to students of foreign language groups - Isakova Ravshana; Begmatova Navruza; Otajonova Firuza (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001